Salt template-assisted polymer tethering strategy to achieve high dispersed cobalt single atoms/clusters on porous carbon catalysts for effective Fenton-like reactions - Song, Jiaojiao; Wang, Ruiyan; Wang, Jiale; Hu, Yi; Guan, Jiaxuan; Li, Yang; Xu, Xiangjian; Zhou, Qi (Journal of environmental chemical engineering, 2024)
The exploration of the synthesis of porous carbon-supported metal nanocatalysts with high metal loading and dispersion for the development of heterogenous catalysts is important. However, this remains a challenging subject. In this paper, a salt template-assisted polymer tethering strategy was proposed to prepare Co single atom and ultrafine cluster anchored on porous carbon (Co-NPC) with a high-loading of 16.9 wt%, thereby exposing high density of reaction sites. The obtained Co-NPC catalyst exhibited excellent catalytic performance for almost 100 % degradation of bisphenol A (BPA) within 20 min, which is much faster than the CoSA-NPC catalyst with only single atom sites and Co-NC without salt template added. Radical quenching experiments and electron paramagnetic resonance tests verified that both the nonradical oxidation pathway by 1O2, the electron transfer and radical oxidation pathway by •OH, SO4•- appeared during the degradation process. After 3 cycles, the removal rate of BPA did not decrease significantly. The fixed bed experiment revealed that Co-NPC could realize the continuous degradation of methylene blue (MB) with almost 100 % degradation efficiency. This research indicated that the strategy by pyrolyzing metal coordinated polymer is a potential method for the synthesis of high metal loading catalyst at gram scale, meeting the requirement of practical applications. [Display omitted] •Co-NPC with high Co loading and dispersion is obtained by polymer tethering strategy.•Single Co atoms and ultrafine clusters are co-existed on the Co-NPC catalyst.•Co-NPC shows better performance for PMS activation than the CoSA-NPC and Co-NC.•ROS were produced through multiple reaction pathways on different sites of Co-NPC.•Fukui function and HPLC-MS were employed to uncover degradation pathways.